PENGARUH PELATIHAN, KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEMERINTAH KABUPATEN LABUHANBATU UTARA. SUMATERA UTARA - Aidil Syahril Hasibuan; Muhamad Arief Noor; Moh Fayruz (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2023)
This study aims to examine and analyze the impact of training, communication, and work motivation on employee performance at the Government Office of Labuhanbatu Utara Regency. This research is quantitative in nature. The sampling technique used is saturated sampling, with a total of 74 respondents. Data obtained were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests, and the coefficient of determination test, utilizing SPSS (Statistic Package for the Social Sciences). The results of partial testing show that training has a significant effect on employee performance, communication has a significant effect on employee performance, and work motivation has a significant effect on employee performance. Meanwhile, simultaneous testing indicates that training, communication, and work motivation collectively have a positive and significant effect on employee performance at the Government Office of Labuhanbatu Utara Regency. The originality of this research lies in its focus on the combined influence of these variables on employee performance in a governmental setting. The findings imply that enhancing training, communication, and motivation can significantly improve employee performance